1998
DOI: 10.1111/j.1469-8749.1998.tb12342.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of selenium deficiency on cardiac function of individuals with severe disabilities under long‐term tube feeding

Abstract: Eleven orally fed (group A) and 14 tube‐fed patients (group B) with severe disabilities and neurological disorders were compared to determine whether selenium (Se) deficiency is present in patients undergoing long‐term tube feeding, and to examine if Se supplementation has beneficial effects on their cardiac function. Assessments of Se intake, serum levels of Se, and cardiac‐function analysis including chest X‐ray, electrocardiography (ECG), and M‐mode echocardiography (UCG) were made. For group B, the effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Dietary supplementation of 100 µg Se (sodium selenite) in patients submitted to total parenteral nutrition was shown to revert arrhythmias and cardiomegalies and lead to an increase in left ventricle ejection fraction (Saito et al 1998). In addition, the incidence of Keshan disease, an endemic dilated congestive myocardiopathy in areas of Se deficiency in China and Russia, has been shown to be prevented by oral Se supplementation at a dosage of 150-300 µg/week (Reeves et al 1989).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dietary supplementation of 100 µg Se (sodium selenite) in patients submitted to total parenteral nutrition was shown to revert arrhythmias and cardiomegalies and lead to an increase in left ventricle ejection fraction (Saito et al 1998). In addition, the incidence of Keshan disease, an endemic dilated congestive myocardiopathy in areas of Se deficiency in China and Russia, has been shown to be prevented by oral Se supplementation at a dosage of 150-300 µg/week (Reeves et al 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Gomez et al (2002) have also reported an increased severity of myopathy in Se-depleted chronically infected mice; furthermore, Davis et al (1998) showed that Se supplementation reduced parasitaemia and mortality in infected mice. Based on these findings and taking into account the association of Se intake with the prevention of cardiac diseases (Korpela et al 1989, Reeves et al 1989, Foster & Sumar 1997, Saito et al 1998, we investigated the effect of Se treatment on the development of chronic cardiopathy in T. cruzi-infected mice in both prevention and reversion schemes.…”
mentioning
confidence: 99%
“…Dietary supplementation of 100  μ g Se (sodium selenite) in patients receiving total parenteral nutrition has been reported to prevent arrhythmias and cardiomegaly and lead to an increase in left ventricle ejection fraction [36]. In addition, the incidence of Keshan disease, an endemic dilated congestive myocardiopathy in areas of Se deficiency in China and Russia, has been shown to be decreased by oral Se supplementation at a dosage of 150–300  μ g/week [36, 37].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the incidence of Keshan disease, an endemic dilated congestive myocardiopathy in areas of Se deficiency in China and Russia, has been shown to be decreased by oral Se supplementation at a dosage of 150–300  μ g/week [36, 37]. It should be noted that Se supplementation has also been suggested as a strategy for prevention of myocardial disease in other studies of human cardiac pathology [3638]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation